Amphibians and reptiles, Romblon Island group, central Philippines: comprehensive herpetofaunal inventory - Cameron Siler (Check List, 2012)
We present results from several recent herpetological surveys in the Romblon Island Group (RIG), Romblon Province, central Philippines. Together with a summary of historical museum records, our data document the occurrence of 55 species of amphibians and reptiles in this small island group. Until the present effort, and despite past studies, herpetological diversity of the RIG and their biogeographical affinities has remained poorly understood. We report on observations of evolutionarily distinct amphibian species, including conspicuous, previously known, endemics like the forest frogs Platymantis lawtoni and P. levigatus and two additional suspected undescribed species of Platymantis. Moderate levels of reptile endemism prevail on these islands, including taxa like the karst forest gecko species Gekko romblon and the newly discovered species G. coi. Although relatively small and less diverse than the surrounding landmasses, the islands of Romblon Province contain remarkable levels of endemism when considered as percentage of the total fauna or per unit landmass area.